ANALISIS PENERAPAN SOP SURAT MASUK PADA PT XYZ - Muhammad Rafli; Christian Wiradendi Wolor; Maulana Amirul Adha (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
This research was conducted at PT XYZ, which aims to determine the application of incoming mail SOPs to PT XYZ's Dynamic Archives Subsection and to find out whether the implementation of these SOPs has been carried out optimally. This research is a qualitative research with data collection methods through observational studies, interviews and documentation with informant taking techniques using purposive sampling with a total of 4 participants. The results obtained in this study stated that the management of incoming mail at the PT XYZ Dynamic Archives Subdivision was still not in accordance with the applicable SOP. There is a messy Agenda Book Recording, file cabinets that are not given indexes and follow-up units, as well as inadequate distribution equipment. Thus, adequate facilities or equipment are needed in the process of distribution, education and training of employees in managing incoming mail, as well as supervising incoming mail management activities.